(untitled) (Annals of Medical Research, 2021)
Aim: Emergence agitation (EA) is a postanesthetic phenomenon that is common in patients who undergo nasal surgery with general anesthesia, which manifests itself with confusion and violent behaviors and may cause serious problems such as bleeding in the surgical site, unplanned removal of catheter or endotracheal tube. In this study, we aimed to compare the effect of thiopental and ketofol on EA formation after nasal surgery.Material and Methods: This study was performed as a prospective, randomized, single-blind, clinical trial in 80 patients undergoing nasal surgery. The patients were randomly divided into two groups as thiopental (group P:40) and ketofol (group K:40). As the primary outcome; Riker Sedation Agitation Scale (RSAS) was used in order to evaluate EA at the 5th minute after extubation. As the secondary outcome; we aimed to evaluate predisposing factors causing EA.Results: The mean age of the patients was 38.55±13.12 in Group P, while it was 40.68±11.88 in Group K. The incidence of emergence agitation (EA) was significantly higher in Group P than in Group K. There was a statistically significant difference between the two groups (Group P:12 cases (30%), Group K:1 case (2.5%), P:0.001). Residual sedation values in PACU were similar in both groups (P:0.248). The duration of stay in PACU was significantly lower in Group P (P:0.001). Duration of anesthesia, duration of surgery, time to extubation and time to verbal response times were similar in both groups. There was no statistically significant difference between the groups.Conclusion: In patients who underwent nasal surgery under general anesthesia; using ketofol instead of thiopental can significantly reduce EA.